Financial Management of MSMEs Accounting And Tax For Communities Of Productive Age In Kanten, Kebonangung Village, Bantul District - Fuadhillah Kirana Putri; Nur Anita Chandra Putry; Teguh Erawati; Nala Tri Kusuma; Enggar Kartika Cahyaning; Suyanto Suyanto (Universitas Negeri Semarang, 2023)
The President has directed to developing of Micro, Small, and Medium Enterprises (MSMEs) to grow the people's economy. In order to help MSMEs meet their financial reporting needs, the Indonesian Institute of Accountants' Financial Accounting Standards Board (DSAK IAI) compiled and ratified Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM), which became effective on January 1, 2018. However, because of the many conveniences in terms of communication and transactions, many people are still not competent to use it or seek information. So, many of them need to pay more attention to taxes and manage their business accounting. This community service activity aims to improve skills and mindsets that are increasingly advanced and developing, especially in people of productive age, in financial management for each individual in Dusun Kanten RT 004, Kanten, Kebonagung Village, Imogiri District, Bantul Regency. The method used is counselling or socialization in MSME accounting and taxation, as well as managing finances in a productive age. The results of this socialization are increased knowledge, understanding, and development related to the tax sector, micro business accounting, and managing finances at a productive age, as well as providing simple accounting and tax training so that the wider community can manage their finances properly. Presiden RI telah memberikan arahan untuk mengembangkan Usaha Mikro Kecil dan Menengah (UMKM) dalam rangka untuk menumbuhkan ekonomi kerakyatan. Dalam rangka membantu UMKM memenuhi kebutuhan pelaporan keuangannya, Dewan Standar Akuntansi Keuangan Ikatan Akuntan Indonesia (DSAK IAI) menyusun dan mengesahkan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) yang berlaku efektif per 1 Januari 2018. Meskipun banyak kemudahan dalam hal komunikasi dan transaksi, masih banyak pelaku UMKM yang belum cakap dalam memanfaatkannya seperti halnya dalam mencari informasi terkait dengan SAK EMKM. Hal ini mengakibatkan banyak dari mereka melalaikan pajak dan tidak cakap dalam mengelola akuntansi usahanya sendiri. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan keahlian serta pola pikir yang makin maju dan berkembang terutama pada masyarakat dalam usia produktif dalam pengelolaan keuangan bagi masing-masing individu di Dusun Kanten RT 004, Kanten, Desa Kebonagung, Kecamatan Imogiri, Kabupaten Bantul. Metode yang digunakan berupa penyuluhan atau sosialisasi Akuntansi dan Pajak UMKM serta Mengelola Keuangan Usia Produktif. Hasil sosialisasi ini yaitu meningkatnya pengetahuan, pemahaman, dan perkembangan terkait sektor pajak dan akuntansi usaha mikro, mengelola keuangan di usia produktif serta memberikan pelatihan akuntansi sederhana dan perpajakan sehingga para masyarakat luas mampu mengelola keuangannya dengan baik.